Barriers to Pediatric Surgical Care in Low-Income Countries: The Three Delays’ Impact in Uganda - Kakembo, Nasser; Nabirye, Ann; Kisa, Phyllis; Muzira, Arlene; Sekabira, John (Journal of Surgical Research, 2019)
We sought to understand the challenges in accessing pediatric surgical care in the context of the “three delays” model at the Pediatric Surgery Outpatient Clinic (PSOPC) at a tertiary hospital in Kampala, Uganda.An outpatient database was established at the weekly PSOPC. A survey regarding prior healthcare visits and barriers to care was additionally administered to clinic patients and inpatients.Patients first sought healthcare a median of 56 d before the current visit to the PSOPC. A majority (52%) of patients first sought care at another health facility, and 17% of those surveyed had presented to the PSOPC three or more times for their current medical issue. Of 240 patients with a new issue or due for their next surgery, 10% were admitted to the ward, with only 54% receiving definitive care. Included in the most commonly needed surgeries for PSOPC patients were herniotomy (16% inguinal; 14.9% umbilical), orchiopexy (6.3%), posterior sagittal anorectoplasty (6.3%), and colostomy closure (4.4%), with the range of patient ages at the time of presentation reflecting delays in care. Patient expenditures associated with travel to the hospital showed inpatients coming from significantly further away, with higher costs of travel and need to borrow or sell assets to cover travel costs, when compared with PSOPC patients.Patients face significant delays in accessing and receiving definitive surgical care. Associated burdens associated with these delays place patients at risk for catastrophic health expenditures. Infrastructure and capacity development are necessary for improvement in pediatric surgical care.
Keywords: Pediatric surgery; Uganda; Burden of disease; Access to care; Low and middle-income countries